The Effect of Work Environment, Work Motivation, and Job Training on Employee Performance with Work Discipline as an Intervening Variable at PT Telkom Akses Semarang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the influence of work environment, work motivation, and job training on employee performance, with work discipline as an intervening variable at PT. Telkom Akses Semarang. The population of this research consists of 400 employees of PT. Telkom Akses Semarang, which is a prominent company in the telecommunications sector. The sampling technique used was purposive sampling, and the sample size of 100 employees was determined using the Slovin formula to ensure a representative sample. Data were collected through questionnaires distributed randomly to the selected respondents to gather comprehensive and reliable information. This study employed a quantitative analysis approach, utilizing Smart PLS as the analytical tool, covering the outer model, inner model, and hypothesis testing to assess the relationships between the variables. The findings indicate that the work environment, work motivation, and job training significantly affect employee performance at PT. Telkom Akses Semarang. Furthermore, the use of work discipline as an intervening variable also mediates the influence of work environment, work motivation, and job training on employee performance, suggesting that work discipline plays a crucial role in enhancing overall employee productivity and organizational success.